Molecular immuno‐imaging improves tumor detection in head and neck cancer. Issue 1 (16th December 2021) - Li, Jing‐Hui; Forghani, Reza; Bure, Lionel; Wojtkiewicz, Gregory R.; Wu, Yue; Iwamoto, Yoshiko; Ali, Muhammad; Li, Anning; Wang, Cuihua; Jalali Motlagh, Negin; Papadakis, Andreas I.; Pusztaszeri, Marc P.; et al.
Abstract: Detection and accurate delineation of tumor is important for the management of head and neck squamous cell carcinoma (HNSCC) but is challenging with current imaging techniques. In this study, we evaluated whether molecular immuno‐imaging targeting myeloperoxidase (MPO) activity, an oxidative enzyme secreted by many myeloid innate immune cells, would be superior in detecting tumor extent compared to conventional contrast agent (DTPA‐Gd) in a carcinogen‐induced immunocompetent HNSCC murine model and corroborated in human surgical specimens. In C57BL/6 mice given 4‐nitroquinoline‐N‐oxide (4‐NQO), there was increased MPO activity in the head and neck region as detected by luminol bioluminescence compared to that of the control group. On magnetic resonance imaging, the mean enhancing volume detected by the MPO‐targeting agent (MPO‐Gd) was higher than that by the conventional agent DTPA‐Gd. The tumor volume detected by MPO‐Gd strongly correlated with tumor size on histology, and higher MPO‐Gd signal corresponded to larger tumor size found by imaging and histology. On the contrary, the tumor volume detected by DTPA‐Gd did not correlate as well with tumor size on histology. Importantly, MPO‐Gd imaging detected areas not visualized with DTPA‐Gd imaging that were confirmed histopathologically to represent early tumor. In human specimens, MPO was similarly associated with tumors, especially at the tumor margins. Thus, molecular immuno‐imaging targeting MPO not only detects oxidative immune response in HNSCC, but can better detect and delineate tumor extent than nonselective imaging agents. Thus, our findings revealed that MPO imaging could improve tumor resection as well as be a useful imaging biomarker for tumor progression, and potentially improve clinical management of HNSCC once translated.